Preparation, and Assessment of Antidermatophyte Activity of Miconazole–Urea Water-Soluble Film - Mady, Omar Y.; Al-Madboly, Lamiaa A.; Donia, Ahmed A. (Frontiers in Microbiology, 2020)
Cutaneous mycoses, particularly tinea pedis caused by Trichophyton rubrum, are commonly known infections in humans. They are still considered as a major public health problem worldwide affecting the quality of life due to prolonged period of treatment and development of drug resistance, which leads to recurrence of infections. The objective of our study was to assess the effectiveness of miconazole in the presence and absence of urea, as a penetration enhancer, against T. rubrum and to formulate both of them in a water-soluble film to be applied topically for the purpose of treating tinea pedis caused by this fungus. Drug combination revealed synergism where miconazole minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) (0.5 and 1 mg/L) were considerably declined to 0.001 and 0.004 mg/L, respectively, when combined with 20% urea. This enhanced drug interaction activity against the test strain was explained by the alterations raised on the morphology and ultrastructures observed microscopically. Minimal fungicidal dose of miconazole/urea combination displayed plasmolysis and shrink cytoplasm; however, necrotic cells with punctured walls and degraded cytoplasmic content were observed at high fungicidal dose. Water-soluble films, prepared using increasing values of miconazole MFC and urea, were transparent, smooth, uniform, and flexible. Their physicochemical characters showed homogeneity in weight, thickness, drug content, and folding endurances with normal surface pH values, indicating the reproducibility of the preparation method. The novel simulation model for the film mechanism of action supported the idea and the suggested application method of the new dosage form. Evaluation of these films was carried in vitro using disk diffusion assay as well as in vivo using guinea pig dermatophytosis model. The in vitro assessment revealed an increase in the inhibition zone diameters in a concentration-dependent manner upon using 10 or 20% of urea combined with miconazole. In vivo test showed that combination of 0.004 mg/L miconazole with 20% urea (M + U20) showed the highest efficacy percentage (95.83%), which was statistically superior to the infected untreated control (p < 0.001) in fungal burden reduction as well as improvement in clinical scores (p < 0.001). This work supports the hypothesis and suggests a new promising dosage form for the treatment of T. rubrum infections.